HGF/C-Met Expression in Epithelial Ovarian Carcinogenesis and Its Potential as Molecular Targeted Therapy - Angeline Maranata; Tantri Hellyanti; Ria Kodariah (Indonesian Journal of Cancer, 2023)
Background: The Mesenchymal-Epithelial Transition factor (C-Met) is a tyrosine kinase receptor (TKR) that binds to a ligand called Hepatocyte Growth Factor (HGF). Recent studies conducted on patients with epithelial ovarian cancer (EOC) reported that high expression of C-Met was associated with poorer clinicopathological grading and outcomes. Therefore, this study aimed to further explore the downstream pathway specifically activated when the HGF/C-Met complex was formed, the interplay between C-Met and other molecules, as well as the impact on EOC when these interactions were inhibited through designated molecular targeted therapy.Methods: The search strategy using the PubMed search engine (https://pubmed.ncbi.nlm.nih.gov/) was conducted on September 21, 2022, with the keywords: “HGF/C-Met and ovarian cancer”. The search resulted in 261 articles, and they were filtered by “published in the last five years,” which yielded 67 articles. These articles then underwent further screening, resulting in 40 articles for analysis. A systematic literature review was conducted to improve the quality of this study. Approximately 150 articles were thoroughly examined and organized using a reference manager, then 15 with the greatest impact and clinical relevance to this study were selected. Results: The HGF/C-Met complex was found to stimulate signaling pathways linked to the growth of epithelial cells and also caused the phosphorylation of tyrosine residues on other tyrosine receptors. The activation of C-Met affected the downstream pathways involving molecules associated with cell proliferation and survival, such as epidermal growth factor receptor (EGFR), p53, and KRAS. C-Met can be combined with other tyrosine kinase inhibitors in chemotherapy to enhance the initiation of cell death (apoptosis) in cancer cells.Conclusions: The HGF/C-Met mediated a signaling cascade that played an essential role in the tumorigenesis of ovarian carcinoma and had the potential to be a targeted molecular therapy in EOC